Pregnancy Outcome in First 50 SARS-Cov-2 Positive Patients at Our Center - Madhusudan Dey; Sanjay Singh; Ravindu Tiwari; Vinod G Nair; Devendra Arora; Shyamji Tiwari (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: Suppressed immune system and physiological changes in pregnancy put pregnant women vulnerable to various viral diseases. Various studies have reported adverse pregnancy outcomes in SARS-CoV-2 infection. This study aimed to evaluate the maternal and fetal outcomes in SARS-CoV-2 affected pregnancies at our set up.